Maḥabbah’s Mediating Role in Marine Ethics and Sustainability Practices - Ahmiati Ahmiati; Syaparuddin Razak; Jumarni Jumarni (Pattimura Proceeding, 2026)
Marine ecosystem sustainability in coastal regions is increasingly challenged by climate change, overexploitation of marine resources, pollution, and weak community-based conservation, particularly in Muslim-majority societies where spiritual values shape everyday behavior but remain underrepresented in empirical sustainability studies. This study aims to examine the mediating role of maḥabbah (spiritual love and compassion in Islamic ethics) in the relationship between environmental ethics, marine resource utilization, marine protection, and marine ecosystem sustainability. Grounded in Islamic Environmental Ethics and Compassionate Conservation Theory, the research employs a quantitative explanatory design using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected from 150 Muslim millennial fishers in South Sulawesi, Indonesia, through stratified random sampling. The findings reveal that maḥabbah has a strong and significant direct effect on marine ecosystem sustainability and significantly mediates the effects of environmental ethics, sustainable marine resource utilization, and marine protection practices. These results indicate that internalized spiritual–ethical values play a crucial role in transforming ethical awareness and conservation practices into sustained pro-environmental behavior. The study contributes theoretically by empirically positioning maḥabbah as a mediating construct within sustainability models and practically by offering a value-based framework for strengthening community-driven marine conservation policies in Muslim coastal contexts.